Eureka! discoveries - "Llewellyn, Claire" (Kingfisher London, 2004)
Eureka! Discoveries delves into remarkable moments of revelation across various fields, including archaeology, exploration, natural history, and astronomy. The book highlights significant findings such as the opening of Tutankhamun's tomb, the discovery of the world's oldest bird fossil, the unearthing of a 5,000-year-old mummy preserved in European ice, and the events leading to the 1848 Gold Rush. Through engaging narratives and vivid illustrations, it captures the excitement and impact of these groundbreaking discoveries.